The ultrastructure of spermatozoa of two species of Aegla (A. parana and A. quilombola) (Crustacea, Decapoda) endemic to Brazil - Wolf, Milena R. [UNESP] (2023)
The previously published ultrastructure of Aegla spermatozoa contributed to the phylogenetics of this unique taxon. The present study describes the spermatozoa of two additional aeglids, Aegla parana and A. quilombola. The spermatozoa consist of two hemispheres of the approximate same size and a bilayered acrosomal vesicle; both characteristics of the genus Aegla. The similarity of spermatozoa ultrastructure observed between A. parana and A. quilombola and the endemic Australian anomuran, Lomis hirta (Lomidae) reflects a sister group relationship, even though both are from different regions of the world and different environments today. Aeglid spermatozoa share the same organization with Lomis including the two equal size hemispheres separated by a membrane also two layers in the acrosomal vesicle with the external layer being surrounded by another membrane. The number of spermatozoa microtubular arms is unclear in Aegla, however, they are present in both the nucleus and cytoplasm. This observation does not agree with the presence of spermatozoa arms only in the nucleus, as an exclusive character for Aegla, as proposed previously. The presence of lipid-droplets and peroxisomes was observed only in the spermatozoa of A. quilombola. The greatly reduced number of spermatozoa observed in all specimens analyzed raises concerns about the conservation of several threatened species. In addition, the absence of any spermatophores seems to be a characteristic of the Aeglidae to date.